Unified performance analysis with exact solutions for uplink non-orthogonal multiple access system-based cellular networks - Bulut, Ibrahim Serhat; Ilhan, Haci; Gatera, Omar (WILEY, 2023)
This research presents a unified performance analysis methodology for the power domains of uplink non-orthogonal multiple access (NOMA) system consisting of a base station and an arbitrary number of users over Rayleigh fading channels. The study derives exact closed-form expressions for key performance metrics, such as outage probability (OP), symbol error rate (SER), outage capacity (OC), average channel capacity (AVC), and amount of fading, using binary phase shift keying (BPSK) and quadrature phase shift keying (QPSK) modulations. The analysis encompasses all necessary channel parameters for evaluating the performance of an uplink NOMA system. The theoretical and simulation results completely supported one another. Furthermore, the results were compared with experiments in the literature using similar parameters. The proposed system was determined to increase performance by 40% for OP, 62% for SER, and 4.74 times for AVC at SNR = 20 dB. Finally, this study introduced exact solutions that can significantly accelerate NOMA systems analysis by exploiting the information in the existing database for analytical design processes in communications theory. In this system, all users transmit their signals over Rayleigh channels with equal power, independent and identical distribution in the same time slot and frequency band. However, the base station receives each user's signal at different power due to the distance of the users from the base station (Pathloss). Therefore, the base station separates the received signals with a perfect SIC algorithm, exploiting different power levels. The base station decodes from the strongest signal to the weakest signal.image
Keywords: amount of fading; average channel capacity; non-orthogonal multiple access; outage capacity; outage probability; Rayleigh fading channel; symbol error rate; RESOURCE-ALLOCATION; IOT NETWORKS; NOMA SYSTEM; DOWNLINK; POWER; Engineering; Telecommunications